2012
DOI: 10.1097/phm.0b013e31823d5376
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Activity and Participation of Children and Youth with Disability in Sweden

Abstract: The results from secondary analyses provide preliminary support for the use of a third qualifier measuring subjective experience of involvement to facilitate the split between activity and participation in the International Classification of Functioning, Disability and Health, Children and Youth version, activity and participation domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 9 publications
6
70
0
2
Order By: Relevance
“…The first three chapters showed low representation: Learning and applying knowledge (d1); General tasks and demands (d2); and Communication (d3). These findings support those in previous studies [1,7,26], indicating that the first chapters include basic skills that are important across areas of functioning and constitute prerequisites for involvement in most life situations.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The first three chapters showed low representation: Learning and applying knowledge (d1); General tasks and demands (d2); and Communication (d3). These findings support those in previous studies [1,7,26], indicating that the first chapters include basic skills that are important across areas of functioning and constitute prerequisites for involvement in most life situations.…”
Section: Discussionsupporting
confidence: 82%
“…In concordance with the ongoing debate about the construct of participation as context-dependent and closely related to socially and culturally defined roles [7,15,52], the findings showed a strong connection between the childrens' participation and the social environment. As people around children with SD most often mandate their involvement in ELS, it is a challenge for the adults to support the children by acting as facilitators of participation rather than barriers.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It has been suggested that because capacity does not reflect context it is perhaps most closely linked to the concept of activity, while performance reflects contextual influences and may therefore conceivably be related to both activity and participation (Granlund et al in press). As such, when construed within the notion of performance, participation may, in part at least, be assessed in terms of the frequency of involvement in everyday activities (Adolfsson, Malmqvist, Pless, & Granuld, 2011;Granlund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%